The Thiazide-Sensitive Co-Transporter Promotes the Development of Sodium Retention in Mice with Diet-Induced Obesity - Matthew R P Davies; Kurt Gleich; Marina Katerelos; Mardiana Lee; Peter F Mount; David A Power (Karger Publishers, 2015)
Background/Aims: Intravascular volume expansion due to sodium retention is involved in the pathogenesis of obesity-related hypertension. Institution of high fat diet (HFD) feeding leads to an initial state of positive sodium balance due to enhanced tubular reabsorption of sodium, but which tubular sodium transporters are responsible for this remains undefined. Methods: C57/Bl6 mice were fed control or HFD for 3 weeks. Blood pressures were recorded by tail cuff method. Sodium transporter expression and phosphorylation were determined by Western blotting. In vivo activity of NCC was determined using natriuretic responses to hydrochlorothiazide. Expression of NCC mRNA was determined using qPCR. Results: At 3 weeks HFD mice had significant weight gains compared to control mice, but blood pressures were not yet elevated. There were no changes in expression or phosphorylation of the bumetanide-sensitive cotransporter, NKCC2, or in expression of subunits of the amiloride-sensitive ion channel, ENaC. However, there were significant increases in mRNA and protein expression of the thiazide-sensitive co-transporter, NCC, in kidneys from HFD mice. Consistent with this, HFD mice had increased in vivo activity of NCC. Conclusions: Increased expression of NCC promotes the sodium loading response to institution of HFD feeding before onset of hypertension.